Hidden hazard weight analysis and safety assessment of fire protection in residential areas - Zhao Jingyu; Li Rui; Song Jiajia; Yang Xiaocheng; Shu Chi-Min (E3S Web of Conferences, 2023)
To evaluate the current situation of fire safety in domestic high-rise residential communities, the community, which integrates high-rise residential buildings, office buildings, and shops, was deliberately selected as an example to conduct fire safety assessment. Combined with the current domestic and foreign fire safety assessment methods and practical application of the review, the establishment of the community at all levels of the evaluation index system, the use of analytic hierarchy process (AHP) for fire safety assessment of the community. Results showed that the fire hydrant system and automatic fire alarm linkage system played a decisive role in the fire safety of the community. To perfect community fire safety assessment, and reduce the plot to fire safety risk, enhance the level of community comprehensively, can not only enhance residents on fire control safety knowledge, and the exact analysis of problems existing in the community fire and handled in time, but also strengthen fire safety management, enhanced the safety awareness of the people.